Spatial pattern and determinants of anemia among women of childbearing age in Nigeria. (February 2021) - Ogunsakin, Ropo Ebenezer; Akinyemi, Oluwadare; Babalola, Bayowa Teniola; Adetoro, Gbemisola
Highlights: We explore spatial patterns of anemia among women of childbearing age in Nigeria. Model estimation and the inference was fully Bayesian approach via integrated nested Laplace approximations (INLA). Findings divulge substantial spatial variations in the likelihood of the disease. Abstract: Background: The risk of anemia in Nigeria is of public health importance, with an increasing number of women of reproductive age being anemic. This study sought to identify the spatial distribution and examine the geographical variation of anemia risk at a regional level while accounting for risk factors associated with anemia among women of childbearing age in Nigeria. The significant interest in spatial statistics lies in identifying associated risk factors that enhance the risk of infection. However, most studies make no or limited use of the data's spatial structure and possible non-linear effects of the risk factors. Methods: The data used in this study were extracted from the 2015 Nigeria Demographic and Health Survey (NDHS). A full Bayesian semi-parametric regression model was fitted to data to accomplish the aims of the study. Model estimation and the inference was fully Bayesian approach via integrated nested Laplace approximations (INLA). The fixed effects were modeled parametrically; non-linear effects were modeled non-parametrically using second-order random walk priors. Results: Wealth index, level of education, type of residence, and unprotected drinking water source were found to be the risk factors associated with anemia. The risk of anemia was found to vary across different regions, with North Central, North East, and North West regions having the highest number of cases and South East with the least number of cases. The spatial analysis result indicated that statistically high hot-spots of anemia were observed in all the northern parts of the country. Conclusion: The study revealed associations between anemia risk and women residing in rural settlements, wealth index, women with no formal education, and unprotected drinking water sources. Community and household-related change interventions should, therefore, be pertinent to the prevention of anemia. The spatial analysis further revealed a significant anemia risk towards the Northern areas of Nigeria. We propose that interventions targeting women of reproductive age should initially focus on these regions and subsequently spread across Nigeria.